Sahâbîlerin Kur’ân tefsirinde ehl-i kitap âlimlerinden yararlanmaları - Rakib, Abdullah Muhammad Zaved (My University, 2021)
Hz. Peygamber’le sohbet fırsatı kazanmış olan sahâbîlerin Kur’ân tefsirine katkıları çok büyüktür. Çünkü onlar Kur’ân’ın nüzûlüne tanık oluyorlar; indirilen âyetleri çok iyi anlıyorlardı. Bir sorun çıktığında Hz. Peygamber’in yanına gidip çözüm bulabiliyorlardı. Öte yandan, Medine döneminde Ehl-i kitaptan bazılarının İslam dinini kabul ettiği anlaşılmaktadır. Kur’ân kıssaları, geçmiş peygamberler ve ümmetleri ile ilgili âyetlerin açıklanmasında bu yeni Müslümanların bilgi ve rivâyetlerinden de yararlanılıyordu. Nitekim sahâbîlerden Ebû Hüreyre, Enes b. Mâlik, Ömer b. Hattâb, Abdullah b. Ömer, Abdullah b. Abbas, Abdullah b. Zübeyr ve Muâviye büyük ölçüde Abdullah b. Selâm, Kâ‘b el-Ahbâr ile Vehb b. Münebbih’in rivâyetlerinden Kur’ân tefsirinde yararlanmışlardır. Zaman içerisinde Ehl-i kitap âlimlerin rivâyetleri tefsir kitaplarına intikal etti. Bazı müfessirler bu rivâyetleri sened ve metin açısından ele almışlardır. Dolayısıyla çalışmamızın konusu, sahâbîlerin Kur’ân tefsirinde Ehl-i kitap âlimlerinden yararlanmış olduğu rivâyetlerin tespiti ve değerlendirilmesidir.

The contributions of the Companions who had the opportunity to speak with the Prophet Mohammad to the interpretation of the Quran are great. Because they had witnessed revelation of the Quran; they have delicately understood very well the verses sent down. When a problem arose, they used to go to the Prophet and found the solution. On the other hand, it is understood that some of the People of the Book accepted Islam as religion during Medina period. The information and rumors of these new Muslims were also used to explain the verses about the stories of Quran, prophets from past and their disciple. It worth mentioning that the companions of the Prophet; Abu Hurairah, Anas ibn Malik, Umar ibn al-Khattab, Abdullah b. Umar, Abdullah b. Abbas, Abdullah b. al-Zubayr and Muawiyah were reportedly beneficiaries from the narrations of the People of the Book like Abdullah b. Salam, Kaʽb al-Aḥbār and Wahb ibn Munabbih in the interpretation of the Quran. Furthermore, the narrations of these people were transferred to Quranic commentary books. Some Quran commentators discussed these narratives regardless of script and text. Therefore, this study is the determination and evaluation of the rumors that the Companions made use of from the scholars of the People of the Book in the interpretation of the Quran.
Keywords: Companion of the Prophet; Ehl-i kitap Âlimleri; Hermeneutics; Islam; Isra’iliyyat; İslam; İsrâiliyat; Kur’ân Tefsiri; Quranic Commentary; Sahâbe; Scholar of the People of the Book; Tefsir bilimi; Tradition